The Impact of Developing Tourist Villages on Social Resilience in Sungai Kakap Sub-District, Kubu Raya District - Syarmiati, Syarmiati; Rupita, Rupita; Yulianti, Yulianti; Rahmaniah, Syarifah Ema; Th Musa, Dahniar (International Journal of Education, Vocational and Social Science, 2024)
The development of a tourist village in Sungai Kakap District, Kubu Raya Regency has a significant impact on the social resilience of the local community. This development process not only increases economic potential, but also strengthens social interactions between residents and tourists. First of all, the tourism sector is a new source of income for the community, creating jobs and increasing economic prosperity. This can reduce poverty levels and increase population access to education and health services. Apart from that, the existence of tourist villages creates opportunities for local communities to market their traditional products, increasing added value and sustainability of the local economy. The development of tourist villages also strengthens the social networks of local communities. Interaction between residents and tourists results in an exchange of culture, values and experiences. It enriches people's social lives by introducing them to diverse perspectives and traditions. In this way, tourist villages create an inclusive environment that promotes tolerance and mutual understanding between cultures. The active involvement of residents in welcoming and serving tourists also builds a sense of shared responsibility for the development of the destination. However, it should be remembered that developing tourist villages can also pose challenges, such as the possibility of rapid social change and potential conflicts between local and commercial interests. Therefore, it is important for the government and relevant stakeholders to manage the development of tourist villages wisely, ensuring the right balance between economic growth, cultural preservation and social justice so that the positive impacts can be felt in a sustainable manner by all local communities.